2002
DOI: 10.1081/clt-120014648
|View full text |Cite
|
Sign up to set email alerts
|

Parotitis Due to Organophosphate Intoxication

Abstract: Acute pancreatitis due to pancreatic exocrine over-secretion induced by organophosphate poisoning has been previously reported but parotid gland involvement has not. This paper describes a case of acute organophosphate-induced parotitis in a patient with pre-existing sialolithiasis. The patient developed bilateral facial swelling in the pre-auricular area extending to the angle of the jaw and also developed elevated serum amylase on the second day of the poisoning. Serum lipase remained normal. Autopsy confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
0
10
0
2
Order By: Relevance
“…Several studies have demonstrated some evidence for damage in pancreatic exocrine function after anticholinesterase insecticide intoxication (Gokel et al, 2002;Panieri et al, 1997;Dressel et al, 1979;Lankisch et al, 1990). The stimulation of pancreatic secretion secondary to cholinergic stimulation seems to be responsible for the development of pancreatitis (Kandalaft et al, 1991;Goodale et al, 1993;Weizman and Sofer, 1992;Moritz et al, 1994).…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have demonstrated some evidence for damage in pancreatic exocrine function after anticholinesterase insecticide intoxication (Gokel et al, 2002;Panieri et al, 1997;Dressel et al, 1979;Lankisch et al, 1990). The stimulation of pancreatic secretion secondary to cholinergic stimulation seems to be responsible for the development of pancreatitis (Kandalaft et al, 1991;Goodale et al, 1993;Weizman and Sofer, 1992;Moritz et al, 1994).…”
Section: Discussionmentioning
confidence: 94%
“…Another study, however, found that exposure to malathion resulted in decreased glucose-stimulated insulin secretion accompanied with patchy degenerative changes in the islets of Langerhans (Pournourmohammadi et al, 2007). Similarly, other human and animal studies also found that organophosphorus and carbamate insecticide can cause acute pancreatitis, which potentially influence insulin secretion (Dressel et al, 1978; Gokel et al, 2002; Goodale et al, 1993; Harputluoglu et al, 2003; Hsiao et al, 1996; Kandalaft et al, 1991; Lankisch et al, 1990; Marsh et al, 1988; Moore and James, 1981; Moritz et al, 1994; Panieri et al, 1997; Weizman and Sofer, 1992). …”
Section: Mechanisms Of Insecticide-induced Change In Glucose and Lmentioning
confidence: 85%
“…is losing pancreatic exocrine function (Panieri et al 1997;Gokel et al 2002;Dressel et al 1979;Lankisch et al 1990). …”
Section: Discussionmentioning
confidence: 95%